Juridical Review of the Division of Joint Property After Divorce in Mixed Marriages - Adam Rifandi Hakim; Moh. Nafri; Muh. Rizki Syafaat (Indonesian Research Journal in Legal Studies, 2025)
Mixed marriage, defined as a marriage between an Indonesian citizen (WNI) and a foreign citizen (WNA), is a phenomenon that has been increasing alongside globalization. However, when a divorce occurs in such marriages, complex legal issues emerge, particularly regarding the division of joint property. These complexities arise from differences in the legal systems of the countries involved, including restrictions on property ownership by foreigners in Indonesia as stipulated in the Basic Agrarian Law. The main problem addressed in this study is how the division of joint property after divorce in mixed marriages is regulated and implemented, as well as the obstacles encountered in the process. This research employs a normative juridical method, using a legislative approach and case studies, particularly focusing on Constitutional Court Decision Number 69/PUU-XIII/2015. The results indicate that, although Indonesian law generally regulates the distribution of joint property, its implementation in mixed marriages still faces several challenges. These include differences in legal systems between countries, the requirement for recognition of foreign judgments through exequatur, and provisions prohibiting property ownership by foreigners. Additionally, the absence of a prenuptial agreement complicates the fair distribution of property. This study underscores the importance of reforming national laws and harmonizing them with international law principles, as well as the necessity of a strong understanding of international private law concepts such as lex rei sitae and lex domicilii. Such efforts are essential to ensure legal certainty and justice in the division of joint property following divorce in mixed marriages.